2001
DOI: 10.1016/s0304-3959(00)00382-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the potent analgesic enkephalin-catabolizing enzyme inhibitors RB101 and kelatorphan on respiration

Abstract: We investigated whether the enkephalin-catabolizing enzyme inhibitors RB101 and kelatorphan, which have been shown to be potent analgesics, depress respiration as do opioid analgesics. Ventilation was measured in cats and rodents by the barometric method, in the awake state and during anesthesia. Tissue distribution of the inhibitors was either generalized (RB101, 40-160 mg/kg i.p.), largely restricted by the blood-brain barrier to the periphery (kelatorphan, 0.7-20 mg/kg i.v.), or restricted to the brainstem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…However, the role of dual enkephalinase inhibitors on the noradrenergic and serotoninergic pathways to modulate the descending pain inputs is minimized by the weak tonic release of enkephalins in the brain structures such as locus coeruleus and nucleus raphe magnus (Williams et al, 1987;Boudinot et al, 2001).…”
Section: Chronic Pain When Initiated and Maintained By Various Factomentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of dual enkephalinase inhibitors on the noradrenergic and serotoninergic pathways to modulate the descending pain inputs is minimized by the weak tonic release of enkephalins in the brain structures such as locus coeruleus and nucleus raphe magnus (Williams et al, 1987;Boudinot et al, 2001).…”
Section: Chronic Pain When Initiated and Maintained By Various Factomentioning
confidence: 99%
“…Numerous dual enkephalinase inhibitors (DENKIs) have been developed and were shown to selectively protect in vitro and in vivo the enkephalins and to be very effective on various animal models of pain . The protected enkephalins are devoid of the side-effects of morphine (Noble et al, 2008), because the recruitment of opioid receptors is restricted to enkephalin releasing synapses and ubiquitous with morphine, (Williams et al, 1987;Roques et al, 2000;Boudinot et al, 2001). Among these inhibitors, the amino-phosphinic dual inhibitor PL265 presents the advantages to act only at the peripheral level and shows a long duration of action (Bonnard et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, there was a slight decrease (around 20%) in a respiratory minute‐volume that occurred 15 min after drug administration, but it did not disturb the respiration in the long run. In awake cats, icv administration of RB101 (0.4 mg/mouse) did not influence ventilation …”
Section: Pain Controlmentioning
confidence: 92%
“…The antinociceptive action of this enkephalinase inhibitor during inflammation was limited to the periphery, because icv administration of naloxone‐methiodide only slightly antagonized the action of RB101 (20 mg/kg iv ) in arthritic rats . The influence of RB101 on respiration was assessed by Boudinot et al; it was revealed that this agent (100 mg/kg ip ) during 60 min observation period did not significantly affect ventilation when compared to control. Noteworthy, there was a slight decrease (around 20%) in a respiratory minute‐volume that occurred 15 min after drug administration, but it did not disturb the respiration in the long run.…”
Section: Pain Controlmentioning
confidence: 99%
“…RB101, over a range of antinociceptive doses, administered peripherally in awake and anesthetized mice did not alter ventilation (minute volume) even at high doses, 160 mg/kg (i.p.) (Boudinot et al 2001). In the same study, central administration of a large dose of RB101 into the fourth ventricle of awake cats also did not decrease ventilation as compared with vehicle controls.…”
Section: Pharmacologymentioning
confidence: 99%